Secondary and Independently Operated Security System for Cars - Ko, Mei Ching (Universiti Malaysia Sarawak (UNIMAS), 2020)
Nowadays, there are a lot of car crimes happened in Malaysia. Having an existing car security system is not enough to secure the cars. The car thief easily to bypass the existing system and steal the car unknowingly. The thief knows how to breach the security system because they might be an expert on it. There are various ways to bypass the current car security system, such as disabling the battery, cloning the car keys and etc. In order to solve this problem, a secondary and independently operated security system for cars is proposed. The purpose of this system is to introduce a secondary security system as a backup for the default car security system. Besides, it is also to alert the owner in the shortest possible time so that the owner can take immediate action to stop the crime. Waterfall model is used to develop this system. Thus, this thesis gives an introduction to the system, methodology used, design of system, accomplishments of the system and future improvement of the system. It would be significant that the system could give a great impact to the car owner.